Development of Biotechnology E-Module Loaded with Ethnoscience to Equip Students with Science Process Skills & Science Literacy - Rahmalia, Ulfa Cinta; Sudarmin, Sudarmin; Ellianawati, Ellianawati (Universitas Negeri Semarang, 2025)
Science learning in Curriculum 2013 emphasises the integration of attitudes, knowledge and skills, especially science process skills which include observation, hypothesis formulation, experimental design, data analysis and communication of results. However, students’ science process skills in some parts of Indonesia are still low due to conventional learning methods and lack of local context. This research aims to develop ethnoscience-based biotechnology learning e-modules that integrate local wisdom to improve students’ science process skills and science literacy. The research method used Research and Development (R&D) with the 4D model (define, design, develop, disseminate). The e-module was developed using Canva and Heyzine applications with contextualised practicum and ethnovlog content. Expert validation was conducted to ensure the feasibility of materials and media, as well as instrument reliability and question differentiation tests. The results showed that this e-module is feasible to use, practical, effective, and can improve students’ science process skills and science literacy. The use of ethnoscience-based digital media provides a more meaningful and contextualised learning experience, supporting increased motivation and learning outcomes.